2005
DOI: 10.1021/pr050217y
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Expression ofStreptococcuspyogenesIs Significantly Influenced by Human Plasma

Abstract: During the course of infection, the common human pathogen Streptococcus pyogenes encounters plasma. We show that plasma causes S. pyogenes to rapidly remodel its cellular metabolism and virulence pathways. We also identified a variant of the major virulence factor, M1 protein, lacking 13 amino acids at the NH(2)-terminus in bacteria grown with plasma. The pronounced effect of plasma on protein expression, suggests this is an important adaptive mechanism with implications for S. pyogenes pathogenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 54 publications
(123 reference statements)
3
16
0
Order By: Relevance
“…8B). In a previous study, proteome analysis of S. pyogenes following exposure to human plasma (24) revealed an increase in the expression of C5a peptidase, which is consistent with our data and the hypothesis that the induction of C5a peptidase expression by human serum represents a host-specific adaptation mechanism of human pyogenic streptococcal strains. Growth of the wild-type strain and scpB deletion mutant in human serum.…”
Section: Vol 77 2009supporting
confidence: 92%
“…8B). In a previous study, proteome analysis of S. pyogenes following exposure to human plasma (24) revealed an increase in the expression of C5a peptidase, which is consistent with our data and the hypothesis that the induction of C5a peptidase expression by human serum represents a host-specific adaptation mechanism of human pyogenic streptococcal strains. Growth of the wild-type strain and scpB deletion mutant in human serum.…”
Section: Vol 77 2009supporting
confidence: 92%
“…Interestingly, multiple spots for secreted extracellular proteins C5a peptidase and M1 were present in the proteome of plasma-grown bacteria, but were absent in the proteome of strain AP1 grown in laboratory medium. Concurrent with these data, a truncated variant of M1 protein lacking the N-terminal 13 amino acids of the mature, full-length protein was identified, a finding indicative of post-translational modification of this key virulence factor in response to plasma exposure 39 .…”
Section: Vascular Leakage and Survival Of Gas In Plasma And Bloodmentioning
confidence: 74%
“…To examine the effect of plasma on GAS protein expression, Johansson et al 39 compared the proteomes of serotype M1 strain AP1 cultured in laboratory medium or in human plasma. Expression of 39 protein spots representing 24 unique GAS proteins, was significantly increased in cells cultured in human plasma.…”
Section: Vascular Leakage and Survival Of Gas In Plasma And Bloodmentioning
confidence: 99%
“…During infection, H. ducreyi is likely to be exposed to serum components at the site of ulceration as a consequence of vascular leakage. Several pathogens have been shown to alter gene expression in response to plasma or serum, including Streptococcus pyogenes (31), Enterococcus faecalis (40), and Yersinia pestis (14). We had previously found that neither LspA protein could be detected in CCS when wild-type H. ducreyi was grown in the absence of FCS (data not shown).…”
Section: Discussionmentioning
confidence: 89%